1996
DOI: 10.1164/ajrccm.153.1.8542131
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative capacity of the skeletal muscle and lactic acid kinetics during exercise in normal subjects and in patients with COPD.

Abstract: Early lactic acidosis during exercise and abnormal skeletal muscle function have been reported in chronic obstructive pulmonary disease (COPD) but a possible relationship between these two abnormalities has not been evaluated. The purpose of this study was to compare and correlate the increase in arterial lactic acid (La) during exercise and the oxidative capacity of the skeletal muscle in nine COPD patients (age = 62 +/- 5 yr, mean +/- SD, FEV1 40 +/- 9% of predicted) and in nine normal subjects of similar ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
322
5
12

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(360 citation statements)
references
References 25 publications
21
322
5
12
Order By: Relevance
“…The alternative would be that the ventilatory load progressively increases during exhaustive PPV-assisted exercise. This model would be consistent with progressive carbon dioxide production (and retention) consequent on the loss of oxidative capacity [30], which is a recognized feature of the peripheral myopathy associated with COPD. In this context, it is of interest that the two subjects whose performance showed the greatest improvement with PPV were the two making the greatest use of the (possibly redundant) abdominal muscles during the free walk.…”
Section: Significance Of the Findingssupporting
confidence: 68%
“…The alternative would be that the ventilatory load progressively increases during exhaustive PPV-assisted exercise. This model would be consistent with progressive carbon dioxide production (and retention) consequent on the loss of oxidative capacity [30], which is a recognized feature of the peripheral myopathy associated with COPD. In this context, it is of interest that the two subjects whose performance showed the greatest improvement with PPV were the two making the greatest use of the (possibly redundant) abdominal muscles during the free walk.…”
Section: Significance Of the Findingssupporting
confidence: 68%
“…These findings are in accordance with GEA et al [27], who did not find abnormalities in enzyme capacities in deltoid muscle. However, in studies examining quadriceps femoris muscle, a decreased oxidative capacity as measured by CS [3,6] and HAD [6] and an increased glycolytic capacity as measured by PFK [6] were found. With comparable patient characteristics, other factors seem to be more important in causing the discrepancies between the studies.…”
Section: Discussionmentioning
confidence: 95%
“…JAKOBSSON et al [6] found a decreased oxidative capacity and an increased glycolytic capacity in quadriceps femoris muscle. MALTAIS et al [3] reported a decreased oxidative capacity in quadriceps femoris muscle. In another recent study [4], in tibialis anterior muscle, indications for an imbalance in adenosine triphosphate (ATP) utilization and resynthesis were found, as suggested by increased inosine monophosphate (IMP) levels, which were negatively related with ATP/adenosine diphosphate (ADP) ratios.…”
mentioning
confidence: 95%
“…Physiologic abnormalities in the structure and metabolism of the skeletal muscles have also been shown (Maltais et al, 1996;Casaburi, 2000). Rehabilitation programmes, including physiotherapy (mobility training, breathing exercises and physical exercise), nutritional support, psychotherapy and education, are recommended in international treatment guidelines for COPD patients (Siafakas et al, 1995;Ries et al, 1997).…”
Section: Introductionmentioning
confidence: 99%